Management trajectory for dyscirculatory encephalopathy grade I, associated with idiopathic intracranial hypertension: a cardioneurological case - V. A. Gorshkov-Cantacuzene (Российский кардиологический журнал)
The article presents clinical case of a young woman with dyscirculatory encephalopathy grade I associated with idiopathic intracranial hypertension, with lability of arterial pressure and hypochondria. The uniqueness of the case presented, is in multidisciplinarity of disorders and difficulty in patient management trajectory formulation.